Efektivitas Penegakan Hukum Perjudian Online di Indonesia: Mengatasi Hambatan Regulasi dan Implementasi - Adlina, Nisa Amalina (Indonesian Journal Publisher, 2025)
This study aims to analyze the effectiveness of law enforcement against online gambling crimes in Indonesia by examining regulatory aspects and their implementation. Specifically, it evaluates the inconsistencies in Indonesia’s legal framework governing online gambling and their impact on legal certainty and enforcement effectiveness. This research employs a normative approach by analyzing various laws and regulations, including the Criminal Code (KUHP) and the Electronic Information and Transactions Law (UU ITE), as amended by Law Number 1 of 2024. Data collection is conducted through literature studies and descriptive analysis. The findings reveal significant discrepancies in sentencing provisions between the KUHP and the UU ITE, leading to legal uncertainty and weakening law enforcement efforts. Additionally, other factors such as limited law enforcement resources, technological infrastructure constraints, and societal attitudes further exacerbate the issue. Consequently, efforts to combat online gambling still face major challenges. In conclusion, harmonization of gambling-related regulations and improvements in law enforcement capacity are necessary to enhance the effectiveness of law enforcement against online gambling and to ensure greater legal certainty for society.